2013
DOI: 10.1371/journal.ppat.1003421
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Reassortment Occurs with High Frequency in the Absence of Segment Mismatch

Abstract: Reassortment is fundamental to the evolution of influenza viruses and plays a key role in the generation of epidemiologically significant strains. Previous studies indicate that reassortment is restricted by segment mismatch, arising from functional incompatibilities among components of two viruses. Additional factors that dictate the efficiency of reassortment remain poorly characterized. Thus, it is unclear what conditions are favorable for reassortment and therefore under what circumstances novel influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
237
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(259 citation statements)
references
References 52 publications
(61 reference statements)
19
237
3
Order By: Relevance
“…The probabilities of recovering any particular genotypes eight times within 21 or 23 reassortant viruses purely by chance are 2.7 × 10 −12 and 6.4 × 10 −12 , respectively, indicating that genetic reassortment between the EN and MO viruses is strongly biased. In comparison, a recent study of the genetic reassortment of influenza viruses differing only by two or three silent mutations in the middle of the gene segments demonstrated a high reassortment rate (88.4%), and the 123 different reassortant genotypes obtained from 241 purified viruses revealed no particular association between gene segments (37).…”
Section: Discussionmentioning
confidence: 76%
“…The probabilities of recovering any particular genotypes eight times within 21 or 23 reassortant viruses purely by chance are 2.7 × 10 −12 and 6.4 × 10 −12 , respectively, indicating that genetic reassortment between the EN and MO viruses is strongly biased. In comparison, a recent study of the genetic reassortment of influenza viruses differing only by two or three silent mutations in the middle of the gene segments demonstrated a high reassortment rate (88.4%), and the 123 different reassortant genotypes obtained from 241 purified viruses revealed no particular association between gene segments (37).…”
Section: Discussionmentioning
confidence: 76%
“…The observations of gene dispersal and limited persistence of gene lineages among flyways are likely the result of countless introductions and subsequent removals of single gene lineages introduced by reassortment to AIVs in other flyways (19). The vast majority of reassortment events have negligible effects on AIV fitness and are presumably limited only by the rate at which multiple infections occur in host species (8). However, while it was not observed here, multiple studies have found persistence of entire AIV constellations across migratory seasons, suggesting the possible persistence of a virus in the environment until opportunistic exposure to some naive host species (62)(63)(64), although environmental conditions likely influence this persistence (65).…”
Section: Discussionmentioning
confidence: 99%
“…Influenza A virus is a single-stranded RNA virus of the order Orthomyxoviridae and contains eight separate RNA genomic segments that readily reassort with each other during coinfections to form ever-changing genomic constellations (8). In waterfowl, AIV infections are typically caused by low pathogenic (LP) avian-origin influenza A viruses (5,9; but see reference 10).…”
mentioning
confidence: 99%
“…The importance of multiplicity reactivation during natural infection depends entirely on the prevalence of coinfection in vivo. Although the high frequency of reassortants generated during guinea pig infection demonstrates that coinfection occurs in vivo (4,26,27), its actual incidence is unknown.…”
Section: Significancementioning
confidence: 99%